Implementasi Metode Activity Based Management(ABM) Dalam Meningkatkan Efisiensi dan Profitabilitas Pada UMKM Suka Maju Ajaobaki - Alberth Alfredo Koy; Sarlin Paulina Nawa Pau; Yohanes Demu (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine how the application of the Activity Based Management method at Suka Maju MSMEs in increasing efficiency and profitability. This research also focuses on identifying activities that occur in Suka Maju MSMEs so that value-added activities and non-value-added activities can be identified. The research method used in this research is descriptive qualitative, data collection techniques used are interviews and documentation. Some of the interviewed informants included: Owner of UMKM Suka Maju, Treasurer and Employees The results of this study indicate that Suka Maju MSMEs have not implemented the Activity Based Management method which affects the inefficient activities that occur and has an impact on profits. Activities that do not provide added value and are not yet effcient are the selection of raw materials and cleaning of raw materials.